Analisis Perbaikan Jatuh Tegangan pada Penyulang Distribusi Primer 20 kV: Analysis Of Voltage Drop Repair On Primary Distribution Feeders 20 kV - Simarmata, Lewi; Mangindaan , Glanny; Patras, Lily (Universitas Sam Ratulangi, 2024)
Abstract — Biak District is currently experiencing a period of development of long-term infrastructure development which includes the construction of tourism, industry, manufacturing, to the construction of national housing spread across Biak Regency. So that the forecasting of large electrical loads in the next ten years in 2033 will rise to 23.21%, so that the value of the voltage drop in 2033 precisely at the Karbos feeder reaches 25.85% with the received voltage at the end of the line reaches 6,299 kV. As for karmar feeders, the voltage drop value in 2033 can reach 11.9% with the receiving voltage at the end of the line reaching 14,087 kV. It is necessary to make improvements with the addition of power capacitors on the main line of the line so that the voltage profile in 2033 can be in accordance with the permitted PLN standards. The capacitor that needs to be added to the carbos feeder is 500 kVAR and the karmar feeder capacitor is added by 150 kVAR. After the addition of Power Capacitors, The Voltage value received at the end of the line becomes 19.31 KV at Karbos feeders and 19.25 kV at Karmar feeders, so that the voltage profile at Karbos and Karmar feeders in 2033 is in accordance with the permissible PLN standards. Key words — Forecasting Load; Power Capacitors; Voltage Drop] Voltage Profile Abstrak — Kabupaten Biak saat ini sedang mengalami masa pengembangan pembangunan insfrastruktur jangka panjang yang meliputi pembangunan parawisata, industri, pabrikan, hingga pembangunan perumahan nasional yang tersebar di Kabupaten Biak. Sehingga perkiraan besar beban listrik dalam sepuluh tahun ke depan yaitu pada tahun 2033 akan naik mencapai 23.21%, sehingga besar nilai jatuh tegangan pada tahun 2033 tepatnya di penyulang Karbos mencapai 25.85% dengan tegangan terima pada ujung saluran mencapai 6.299 kV. Sedangkan untuk penyulang Karmar nilai jatuh tegangan pada tahun 2033 dapat mencapai 11.9% dengan tegangan terima pada ujung saluran mencapai 14.087 kV. Maka perlu dilakukan perbaikan dengan penambahan kapasitor daya pada jalur utama saluran agar profil tegangan pada tahun 2033 dapat sesuai dengan standar PLN yang dizinkan. Kapasitor yang yang perlu ditambahkan pada penyulang Karbos sebesar 500 kVAR dan pada penyulang Karmar kapasitor yang ditambahkan sebesar 150 kVAR. Setelah penambahan kapasitor daya didapatkan nilai tegangan yang diterima pada ujung saluran menjadi 19.31 kV pada penyulang Karbos dan 19.25 kV pada penyulang Karmar, sehingga profil tegangan pada penyulang Karbos dan Karmar pada tahun 2033 telah sesuai dengan standar PLN yang diizinkan. Kata kunci — Jatuh Tegangan; Kapasitor Daya; Perkiraan Beban; Profil Tegangan